Aid to agriculture: reversing the decline - von Braun, Joachim; Hopkins, Raymond F.; Puetz, Detlev; Pandya-Lorch, Rajul (International Food Policy Research Institute, 1993)
Despite continuing food crises in the developing world, agricultural development assistance from major governments and international institutions has declined since the early 1980s. Aid to Agriculture: Reversing the Decline, an IFPRI Food Policy Report by Joachim von Braun, Raymond F. Hopkins, Detlev Puetz, and Rajul Pandya-Lorch, addresses the economic, political, and bureaucratic causes of this downward trend and the reasons why reversing this trend is of critical importance for many of the world's poorest countries.